ANALISIS PENGARUH JOB DEMAND DAN WORK FAMILY CONFLICT TERHADAP ORGANIZATIONAL COMMITMENT DENGAN BURNOUT SEBAGAI VARIABEL MEDIASI - Siti Nabila Yuseva; Hendra Lukito; Harif Amali Rivai (Halu Oleo University, 2024)
This research aims to obtain empirical evidence regarding the influence of job demands and work family conflict on organizational commitment through the mediation of burnout. The population in this study were employees of the West Sumatra Financial Services Authority (OJK). The sample collection technique is total sampling, that is, the entire population is sampled. The data analysis technique uses Structural Equation Modeling (SEM) with SmartPLS software. Based on the results of research tests, it shows that job demand has a positive and significant effect on burnout. Work family conflict has no positive and significant effect on Burnout, Job demand has no positive and significant effect on Organizational Commitment of employees, Work family conflict has no positive and significant effect on Organizational Commitment, Burnout has a positive and significant effect on Organizational Commitment. indirectly, Job demand influences Organizational Commitment through Burnout as mediation and Work family conflict does not influence Organizational Commitment through Burnout as mediation West Sumatra Financial Services Authority employees.